Single-component rare earth hafnate ceramic material with low reactivity value loss and preparation method of single-component rare earth hafnate ceramic material
The preparation of single-component rare earth hafnate ceramic materials through solid phase method and vacuum sintering technology solves the problems of high loss of reactivity value and low transmittance of existing control rod materials, and realizes high density, low loss and high transparency ceramic materials, meeting the needs of long-life service and high-performance control rod materials.
Patent Information
- Application Number
- CN202411768006.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing control rod materials have high reactivity value loss and low transmittance during service, so they cannot prepare high transparency hafnate ceramic materials, and the subabsorption and heat performance are insufficient, which affects long-life service.
Highly compact single-component rare earth hafnate ceramic materials are prepared by solid-phase molding and vacuum sintering. The combination of rare earth elements such as Eu, Gd, Tb, Dy, Tm and Hf oxides is used to design five single-component rare earth hafnate ceramic materials to achieve high transparency and low reactivity value loss.
The high density, low reactivity value loss, long service life and high transparency of single-component rare earth hafnate ceramic materials are achieved, meeting the requirements of control rod materials under reactor service conditions.
Smart Images

Figure CN119751055A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nuclear reactor control rod materials, and in particular relates to a low-reactivity value loss single-component rare earth hafniumate ceramic material and a preparation method thereof. Background Art
[0002] Nuclear energy is a major contributor to clean energy, especially in the development of low-carbon energy technology and the global goal of world economic prosperity and stability. The safe and economic operation of current advanced nuclear energy systems depends largely on the performance of fuels and materials. Among nuclear engineering materials, control rods are key components used to compensate and adjust the core reactivity of nuclear power reactors to ensure the long-term safe operation of the core. For control rod materials, first of all, it is required to have a large neutron absorption cross section and a high initial reaction value of the material. Secondly, the control rod material is also required to have a long life, which requires it to contain a large number of absorber nucleons per unit volume and a low reactivity value loss. In addition, it is required that the daughter nucleus formed after absorbing neutrons also has a large absorption cross section, so that its ability to absorb neutrons will not be affected by its own "burnup". Finally, the control rod material is required to have radiation resistance, corrosion resistance, and good mechanical and thermal properties.
[0003] In recent years, some rare earth elements have attracted much attention due to their high neutron absorption cross-section and long neutron burnup chain, and people have been trying to use the (n, γ) reaction of rare earth-based materials to absorb thermal neutrons to replace boron materials. 10 B's (n, α) reaction.
[0004] Traditional control rod materials are mainly made of boron carbide (B4C) or boron steel, silver-indium-cadmium alloy and metal hafnium. Boron carbide (B4C) or boron steel has high neutron absorption capacity and no secondary radiation pollution, but 10 The (n, α) reaction of B will accumulate a large number of irradiation defects, which will then form He bubbles and cause the material to swell, resulting in rod jamming. In addition, the reactivity value loss of boron carbide as a control rod material exceeds 50% within five years, which is too high and the service life is too short. Silver-indium-cadmium (Ag-In-Cd) alloy also has efficient neutron absorption performance and can quickly introduce negative reactivity to shut down the reactor urgently to ensure nuclear safety; however, Ag and In undergo transmutation after absorbing neutrons, resulting in the precipitation of a second phase with lower density, which causes swelling. In addition, the reactivity value loss of silver-indium-cadmium material exceeds 15% within five years of service, which is expensive and too costly. Metal hafnium has a high thermal neutron capture cross section and is resistant to high temperatures and corrosion. However, under the influence of irradiation, hafnium alloys are prone to vacancies and defects, which in turn lead to irradiation swelling and fatigue fracture, greatly reducing the service life and reliability of hafnium alloy control rods.
[0005] For example, patent document CN 114988869 A (publication date: September 2, 2022) provides a rare earth medium-high entropy hafniumate-based ceramic material and a preparation method thereof. The chemical formula of the medium-high entropy rare earth hafniumate ceramic material is: (RE a Tm b Dy c M d )4Hf3O 12 ; wherein RE is selected from at least one of Tb, Ho, and Gd; and M is selected from Eu and / or Er. The hafnium-based ceramic material is prepared by a sol-gel method and is mainly used to improve the radiation resistance of neutron absorption rod materials. However, the hafnium-based ceramic material has a high reactive value loss problem, which affects its service life. At the same time, its transmittance is low, and it is impossible to prepare a hafnium-based ceramic material with high transparency.
[0006] A2B2O7 oxide is considered a promising radiation-resistant material for current and advanced nuclear systems due to its flexibility in crystal structure, ability to accommodate actinides, and excellent thermal stability and chemical durability under extreme conditions. Rare earth hafnium salt RE2Hf2O7 has a high melting point and excellent high-temperature stability. Among them, the Hf element has a high neutron absorption cross section and its daughter nucleus also has a high neutron absorption cross section, such as 177 Hf, which captures a neutron to form 178 Hf, which forms 179 Hf, etc., all of which have large resonance absorption cross sections and have the possibility of long-life service as neutron absorbers.
[0007] For example, patent document CN 115572162 A (publication date: January 6, 2023) provides a rare earth medium high entropy hafniumate ceramic material for reactor neutron control, and the chemical formula of the rare earth high entropy hafniumate ceramic material is: (RE 0.2 Sm 0.2 Eu 0.2 Dy 0.2 Er 0.2 )2Hf2O7, RE is Nd or Gd. The chemical formula of rare earth entropy hafnium oxide ceramic material is: (Sm 1 / 3Eu 1 / 3 G 1 / 3 )2Hf2O7. However, the hafnium oxide ceramic material has the problem of high reactive value loss and low transmittance, and it is impossible to prepare a hafnium oxide ceramic material with high transparency.
[0008] Therefore, how to prepare a ceramic control rod material based on hafnium oxide, so that its preparation process is simple, the reactive value loss is low, the neutron absorption performance is good, the thermal and mechanical properties are excellent, the corrosion resistance is long and the service life is long, and at the same time its transmittance is high and high-transparency hafnium oxide ceramic materials can be prepared, has become an important problem to be solved urgently. Summary of the invention
[0009] The present invention is to solve the above technical problems, thereby providing a low reactivity value loss single-component rare earth hafniumate ceramic material and a preparation method thereof. The technical purpose of the present invention is to prepare a single-component hafniumate ceramic control rod material with a reactivity value loss lower than that of existing materials and meeting the reactor service conditions based on the combination of rare earth elements (such as Eu, Gd, Tb, Dy, Tm) with good neutron absorption performance and radiation-resistant substrate RE2M2O7 (M=Hf) type oxides, and achieve high transparency of the material.
[0010] In order to achieve the above object, the technical solution adopted by the present invention is: a method for preparing a high-density single-component rare earth hafnium salt by solid phase molding combined with vacuum sintering, comprising the following steps:
[0011] (1) Drying rare earth oxide powders (europium oxide, gadolinium oxide, terbium oxide, dysprosium oxide and thulium oxide) and hafnium oxide powders to remove crystal water, mixing them in a certain stoichiometric ratio, ball milling, drying, grinding and sieving to obtain fine powders, calcining the fine powders at 1300-1600° C. for 4 hours to obtain pure phase mixed powders, and after cooling to room temperature, ball milling, drying, grinding and sieving the pure phase powders to finally obtain uniform single-component hafnium salt (Eu2Hf2O7, Gd2Hf2O7, Tb2Hf2O7, Dy2Hf2O7, Tm2Hf2O7) precursor powders with good sintering activity;
[0012] (2) adding the precursor powder obtained in step (1) into a mold, maintaining the pressure at 2 to 6 MPa for 2 to 5 minutes, pressing and molding to form a green embryo, placing the green embryo in a cold isostatic press, and maintaining the pressure at 250 to 300 MPa for 10 to 15 minutes to obtain a dense green embryo;
[0013] (3) placing the dense blank obtained in step (2) in a vacuum environment and sintering it at 1850° C. for 8 hours to obtain a pure phase ceramic, annealing and polishing the obtained pure phase ceramic, and finally obtaining a highly dense single-component hafnium oxide ceramic material.
[0014] In order to explore the reactive value loss of the selected materials, the present invention conducted theoretical preliminary research on single-component, dual-component and multi-component rare earth hafnium salt systems, and calculated the single-component Eu2Hf2O7, dual-component (Eu 1 / 2 ,Gd 1 / 2)2Hf2O7, three components (Eu 1 / 3 ,Gd 1 / 3 ,Tb 1 / 3 )2Hf2O7, four components (Eu 1 / 4 ,Gd 1 / 4 ,Tb 1 / 4 ,Dy 1 / 4 )2Hf2O7 and five components (Eu 1 / 5 ,Gd 1 / 5 ,Tb 1 / 5 ,Dy 1 / 5 ,Tm 1 / 5 The results showed that the initial value of the reactive value loss of hafnium oxide ceramic materials decreased with the increase of components, and the loss within five years also increased with the increase of components. According to the experimental results, single-component hafnium oxides showed better initial performance and lower value loss than multi-component hafnium oxides, among which the loss within five years of Eu2Hf2O7 and Dy2Hf2O7 was only about 5%.
[0015] Therefore, the inventors used single-component RE2Hf2O7 type rare earth hafnate as the structural framework, selected RE-position rare earth elements Eu, Gd, Tb, Dy, Tm based on the high neutron absorption cross section, designed five single-component rare earth hafnate ceramic materials, and successfully prepared hafnate ceramic materials with high transmittance, which not only filled the blank of application research in the field of single-component rare earth hafnate ceramics, but also successfully achieved the transmittance of hafnate ceramic materials reaching more than 92% of the theoretical transmittance. Therefore, the method of the present invention provides an important material that can be used in the control rod field in the future, and obtains a type of neutron absorption material with high density, low reactive value loss, high transparency, and is expected to have a long service life.
[0016] The above-mentioned preparation method provided by the present invention successfully prepares single-component rare earth hafnate (Eu2Hf2O7, Gd2Hf2O7, Tb2Hf2O7, Dy2Hf2O7, Tm2Hf2O7) ceramic materials with high density, high transmittance and low reactivity value loss. Among them, the reactivity value loss of europium hafnate (Eu2Hf2O7) and dysprosium hafnate (Dy2Hf2O7) is as low as about 5% within 5 years, which is expected to achieve the requirement of the reactivity value loss of less than 10% within 15 years proposed by the new control strategy and meet the long service life of the control rod. In addition, the preparation method of the present invention has the advantages of simple process, no need for sintering aids, easy operation and no gas pollution.
[0017] The preparation method of the above-mentioned single-component RE2Hf2O7 type rare earth hafnium oxide ceramic material provided by the present invention is not inspired by the prior art. The hafnium oxide ceramic materials currently developed are generally multi-component materials, and do not involve how to develop single-component materials. Therefore, those skilled in the art have no way of knowing what process conditions need to be paid attention to in the development of single-component materials. When preparing single-component ceramic materials, the above-mentioned scheme provided by the present invention is found to have extremely low reactivity value loss compared with multi-component hafnium oxide ceramic materials, which is not possessed by multi-component ceramic materials; on the other hand, the method of the present invention obtains hafnium oxide ceramic materials with extremely high transparency, which is beyond expectations. The hafnium oxide ceramic materials obtained by the existing methods generally do not have the characteristic of high transparency and are basically opaque ceramic materials.
[0018] Furthermore, in step (1), both the rare earth oxide and hafnium oxide are high-purity oxides with a purity of >99.9%, and the molar ratio of the rare earth oxide to hafnium oxide is 1:2.
[0019] Furthermore, the ball milling process in step (1) is as follows: adding the oxide mixed powder into a nylon ball mill with alcohol as the medium and ball milling for 20 hours, controlling the ball-to-material ratio (mass ratio) of the ball mill to be 27:1, and the ball milling speed to be 300 r / min.
[0020] Furthermore, the drying process in step (1) is: pouring the slurry obtained after ball milling into a glass container and drying it at 70-80° C. for 24 hours.
[0021] Furthermore, the sieving in step (1) is through a 300-mesh sieve.
[0022] Furthermore, in step (3), the vacuum environment is a vacuum degree of 10 -2 ~10 -4 Pa; the annealing temperature is 1300-1400°C, and the annealing time is 3-4h.
[0023] The present invention also provides five single-component rare earth hafnium oxide ceramics prepared by the above method. These ceramic columns have the characteristics of high density, low reactive value loss and long service life.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention prepares powder by solid phase method, which solves the cumbersome process problem of preparing high sintering activity powder in the past, and has the advantages of wide application range, simple operation and good situation;
[0026] (2) The method of the present invention obtains a single-component hafnium salt with excellent low-loss performance, and prepares a hafnium salt ceramic material with high density, high transmittance, and excellent mechanical and thermal properties, which has good application prospects in the fields of reactor control rod materials, magneto-optical deflectors, etc.;
[0027] (3) The present invention uses a single-component hafnium salt pure phase powder as a precursor powder, thereby avoiding the influence caused by phase change during the sintering process, and vacuum sintering has no gas pollution, and the harm to human body and environment is very small. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Theoretically calculated initial reactivity values and losses within five years for five different components of hafnium salts: (a) Changes in the loss of the value of the five components of hafnium salts over time; (b) Change rates of the loss of the value of the five components of hafnium salts over time.
[0029] Figure 2 These are actual pictures of five single-component rare earth hafnium salts (Eu2Hf2O7, Gd2Hf2O7, Tb2Hf2O7, Dy2Hf2O7, Tm2Hf2O7) ceramic samples.
[0030] Figure 3 These are the XRD patterns of five single-component rare earth hafnium oxide ceramics (Eu2Hf2O7, Gd2Hf2O7, Tb2Hf2O7, Dy2Hf2O7, Tm2Hf2O7).
[0031] Figure 4 Mechanical properties of five single-component rare earth hafnates (Eu2Hf2O7, Gd2Hf2O7, Tb2Hf2O7, Dy2Hf2O7, Tm2Hf2O7): (a) hardness and fracture toughness; (b) bulk modulus, Young's modulus and shear modulus.
[0032] Figure 5 Thermal conductivity and thermal expansion coefficient of five single-component rare earth hafnates (Eu2Hf2O7, Gd2Hf2O7, Tb2Hf2O7, Dy2Hf2O7, Tm2Hf2O7): (a) thermal conductivity; (b) thermal expansion coefficient. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described in detail below in conjunction with the embodiments. It is necessary to point out that the following embodiments are only used to explain and illustrate the present invention and are not used to limit the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above invention content still belong to the protection scope of the present invention.
[0034] Example 1
[0035] The sources of the powder raw materials involved in all embodiments of the present invention are as follows:
[0036] Eu2O3 (purity 99.99%, Shanghai Aladdin Biochemical Technology Co., Ltd.);
[0037] Gd2O3 (purity 99.99%, Shanghai Aladdin Biochemical Technology Co., Ltd.);
[0038] Tb2O3 (purity 99.99%, Shanghai Aladdin Biochemical Technology Co., Ltd.);
[0039] Dy2O3 (purity 99.99%, Shanghai Aladdin Biochemical Technology Co., Ltd.);
[0040] Tm2O3 (purity 99.99%, Shanghai Aladdin Biochemical Technology Co., Ltd.);
[0041] HfO2 (purity 99.9%, Beijing Huawei Ruike Chemical Co., Ltd.).
[0042] This embodiment prepares a single-component rare earth hafnium oxide ceramic by a solid phase method combined with vacuum sintering, including the following steps:
[0043] (1) Preparation of precursor powder: europium oxide and hafnium oxide, gadolinium oxide and hafnium oxide, terbium oxide and hafnium oxide, dysprosium oxide and hafnium oxide, and thulium oxide and hafnium oxide were weighed in a stoichiometric ratio of 1:2, added to a nylon ball mill with alcohol as the medium and ball milled (ball milled in ethanol at a speed of 300 r / min for 20 hours to obtain a uniformly mixed slurry, with a ball-to-material mass ratio of 27:1), the obtained slurry was filtered into a glass container, and dried at 70°C for 24 hours. The dried powder was After sieving (300 mesh), it was placed in a muffle furnace and calcined at 1300°C for 4 hours to obtain a single-component rare earth hafnium salt precursor powder. The heating rate was 3°C / min. After cooling to room temperature, the cooling rate was 4°C / min. The obtained powder was then subjected to the same ball milling, drying and sieving as mentioned above to obtain a uniform and sintering-active single-component rare earth hafnium salt (Eu2Hf2O7, Gd2Hf2O7, Tb2Hf2O7, Dy2Hf2O7, Tm2Hf2O7) pure phase precursor powder.
[0044] (2) Molding: A single-component rare earth hafnium salt ceramic blank is obtained by dry pressing combined with cold isostatic pressing. The specific process is as follows: the precursor powder obtained in step (1) is added into a customized metal mold, the mold is placed into a dry press, and the pressure is maintained at 2 MPa for 2 minutes. The blank is then taken out, vacuumed and sealed, and then placed into a cold isostatic press, and maintained at 250 MPa for 10 minutes to obtain a relatively dense blank.
[0045] (3) Sintering: The prepared single-component rare earth hafnium salt compact is placed in a vacuum of 10 -4 Pa vacuum environment and sintered at 1850 °C for 8 hours to obtain a ceramic sample.
[0046] (4) Processing: The sintered ceramics were processed into columns with a diameter of 8.5 mm and a height of 15 mm and discs with a diameter of 12.5 mm and a thickness of 2 mm.
[0047] Example 2
[0048] The single-component rare earth hafnium oxide ceramic was prepared according to the method of Example 1, except that:
[0049] In step (1), drying at 80° C. for 24 hours and calcining in a muffle furnace at 1600° C. for 4 hours;
[0050] In step (2), the pressure is maintained at 6 MPa for 5 minutes and at 300 MPa for 15 minutes to obtain a relatively dense green billet;
[0051] In step (3), at a vacuum degree of 10 -3 The annealing treatment was carried out at 1400°C for 4 hours in a vacuum environment of 1.3 Pa.
[0052] Example 3
[0053] The single-component rare earth hafnium oxide ceramic was prepared according to the method of Example 1, except that:
[0054] In step (1), drying at 80° C. for 24 hours and calcining in a muffle furnace at 1400° C. for 4 hours;
[0055] In step (2), the pressure is maintained at 3 MPa for 3 minutes and at 280 MPa for 12 minutes to obtain a relatively dense green billet;
[0056] In step (3), at a vacuum degree of 10 -2 Pa in a vacuum environment and annealed at 1350°C for 3.5 hours.
[0057] Test Example 1
[0058] The performance of the ceramic samples prepared in Examples 1-3 was tested using the following method:
[0059] X-ray diffraction (XRD, X-2700, Dongfang Yuan, Dandong, China) was performed using nickel-filtered Cu Kα1 radiation. The diffraction patterns were recorded in the range of 2θ (10° to 70°) with a resolution of 0.05° / step.
[0060] Vickers hardness (H V) was measured using the Vickers indentation method (Buehler, Omnimet MHT, Lake Bluff, USA) at loads up to 2 N. Before measurement, the sample surface was carefully polished with diamond abrasive. The Vickers hardness was calculated according to formula (1):
[0061]
[0062] In formula (1), F is the indentation load and d is the diagonal length of the indentation. Each sample was measured 7 times to reduce the experimental uncertainty, and then the average value was calculated.
[0063] The longitudinal (V L ) and transverse (V T )Speed of sound.
[0064] Using V L and V T The following different parameters are calculated:
[0065] Bulk modulus:
[0066] Young's modulus:
[0067] Shear modulus:
[0068] The thermal expansion coefficient of the sintered ceramics was measured using a thermal analyzer (DIL 402Expedis Supreme, NETZSCH, Germany), and the thermal diffusivity (α) of the samples was measured using a laser thermal conductivity meter (LFA 457, NETZSCH, Germany). The thermal conductivity was calculated from the thermal diffusivity, specific heat, and bulk density: where the bulk density ρ was measured using the Archimedean method, and the measured densities were all >97%, and Cp was the specific heat, which was calculated using the Neumann–Cope rule.
[0069] k=αρCp(5)
[0070] Result Example 1
[0071] Taking Example 1 as an example (the results of other examples are not much different), the reactivity value and loss rate of the single-component rare earth hafnium oxide ceramic prepared in the example are as follows: Figure 1 As shown, the initial value of the reactivity value can reach up to 44×10 3pcm, which is 1.3 times the initial value of the existing materials silver-indium-cadmium (Ag-In-Cd) alloy and dysprosium titanate material, and the reactivity value loss rate is as low as about 5% within 5 years, which is much lower than the existing materials B4C (5-year loss>50%), silver-indium-cadmium alloy (5-year loss>15%), and dysprosium titanate material (5-year loss>10%). According to the above calculation results, it is confirmed that the reactivity value loss of the single-component hafnium salt material in Example 1 is better than that of two-component, multi-component and other high-entropy hafnium salt materials, and has a longer service life.
[0072] The actual picture of the single-component hafnium salt (Eu2Hf2O7, Gd2Hf2O7, Tb2Hf2O7, Dy2Hf2O7, Tm2Hf2O7) ceramic block prepared in the embodiment is as follows Figure 2 As shown in the figure, it can be seen that the surface of the sample is flat and smooth without any damage, and the ceramic sample has achieved a high transmittance, among which the transmittance of Tb2Hf2O7 material has reached 92% of the theoretical transmittance, while the transmittance of other ceramic samples is slightly lower, but the difference is not much.
[0073] The XRD pattern of the single-component hafnium salt prepared in the embodiment is as follows: Figure 3 As shown, it is shown that Eu2Hf2O7, Gd2Hf2O7, and Tb2Hf2O7 in the prepared single-component rare earth hafniumate ceramics have a pyrochlore structure, and Dy2Hf2O7 and Tm2Hf2O7 have a defective fluorite structure. At the same time, the characteristic peaks of the five samples have no impurity peaks and have good crystallinity, indicating that the prepared products have complete crystal forms.
[0074] The mechanical properties of the single-component hafnium salt prepared in the embodiment are as follows: Figure 4 As shown, it shows that single-component hafnium salt (Eu2Hf2O7, Gd2Hf2O7, Tb2Hf2O7, Dy2Hf2O7, Tm2Hf2O7) ceramics have high hardness and low toughness, and are brittle materials.
[0075] The thermal properties of the single-component hafnium salt prepared in the embodiment are as follows: Figure 5 As shown, the thermal expansion coefficient of the single-component rare earth hafnium oxide ceramic increases linearly with the increase of temperature, indicating that the prepared sample has excellent high-temperature phase stability, high density, and its thermal conductivity is significantly higher than that of the existing material dysprosium titanate. It can be seen that it is an important material available in the reactor control rod material system in the future.
[0076] Comparative Example 1
[0077] Various ceramic materials prepared in patent CN 114988869 A were tested and found to have transmittances of only 32-43% of the theoretical transmittances.
[0078] Comparative Example 2
[0079] Various ceramic materials prepared in patent CN 115572162 A were tested and found to have a transmittance of only 30-35% of the theoretical transmittance.
Claims
1. A method for preparing a low-reactivity value loss single-component rare earth hafnium oxide ceramic material, characterized in that: The following steps are involved: (1) taking raw material powders of rare earth oxide and hafnium oxide, mixing them according to a stoichiometric ratio, grinding them, calcining the refined powders at 1300-1600° C. for 4 hours to obtain pure phase mixed powders, and after cooling to room temperature, ball milling, drying, grinding and sieving the pure phase powders to obtain uniform single-component hafnium salt precursor powders with good sintering activity; (2) adding the precursor powder obtained in step (1) into a mold, maintaining the pressure at 2 to 6 MPa for 2 to 5 minutes, pressing and molding to form a green embryo, placing the green embryo in a cold isostatic press, and maintaining the pressure at 250 to 300 MPa for 10 to 15 minutes to obtain a dense green embryo; (3) placing the dense blank obtained in step (2) in a vacuum environment and sintering it at 1850° C. for 8 hours to obtain a pure phase ceramic, annealing and polishing the obtained pure phase ceramic, and finally obtaining a highly dense single-component hafnium oxide ceramic material.
2. The preparation method according to claim 1, characterized in that: The rare earth oxides in step (1) include europium oxide, gadolinium oxide, terbium oxide, dysprosium oxide or thulium oxide, and the purity of the rare earth oxides is greater than 99.9%; the single-component hafnium salt precursor powder includes Eu2Hf2O7, Gd2Hf2O7, Tb2Hf2O7, Dy2Hf2O7 or Tm2Hf2O7.
3. The preparation method according to claim 1 or 2, characterized in that: The stoichiometric ratio in step (1) is 1:2 in terms of the molar ratio of rare earth oxide to hafnium oxide.
4. The preparation method according to claim 1 or 2, characterized in that: The rare earth oxide powder and hafnium oxide powder in step (1) are dried to remove crystal water.
5. The preparation method according to claim 1 or 2, characterized in that: In step (1), the raw powders of rare earth oxide and hafnium oxide are ball-milled, dried, ground and sieved to obtain fine powders.
6. The preparation method according to claim 1 or 2, characterized in that: The process of ball milling the pure phase powder in step (1) is as follows: adding the pure phase powder to a nylon ball mill with alcohol as the medium and ball milling for 20 hours, controlling the ball-to-material weight ratio of the ball mill to be 27:1, and the ball milling speed to be 300 r / min.
7. The preparation method according to claim 1 or 2, characterized in that: The drying process in step (1) is as follows: pouring the slurry obtained after ball milling into a glass container and drying it at 70-80° C. for 24 hours; and the sieving is passing through a 300-mesh sieve.
8. The preparation method according to claim 1 or 2, characterized in that: The vacuum environment in step (3) is a vacuum degree of 10 -2 ~10 -4 Pa.
9. The preparation method according to claim 1 or 2, characterized in that: The temperature of the annealing treatment in step (3) is 1300-1400° C., and the annealing time is 3-4 hours.
10. A low-reactivity value loss single-component rare earth hafnium oxide ceramic material prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Rare-earth medium-high-entropy hafnate-based ceramic material as well as preparation method and application thereof
CN114988869A
Rare earth medium-high entropy hafnate ceramic material for reactor neutron control
CN115572162A
Magnetooptical material, manufacturing method therefor, and magnetooptical device
CN105531619A
Control rod absorber material and preparation method thereof
CN114044672A
Rare earth hafnate ceramic material as well as preparation method and application thereof
CN115108828A